Cutis Marmorata Telangiectatica and Chiari Type I - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2003)
A 10-year-old girl born with telangiectasias of the lip, trunk, extremities, palms, and soles was found to have an asymptomatic Chiari I malformation without syringomyelia on MRI, and is reported from Children's Hospital, Alabama.